Основні змістовні межі дослідження культурної дилеми індивідуалізм–колективізм - Романуцький, В.М. (Культура народов Причерноморья, 2013)
У статті окреслено основні змістовні межі дослідження дилеми індивідуалізм–колективізм
як основного виміру культурної варіативності. Особливу увагу приділено ключовим поняттям
дослідження, зокрема визначенню універсальних ціннісно–культурних дефініцій у межах співвідносних
параметрів, які представлені у відповідних наукових напрацюваннях; визначенню актуальності
дослідження даних конструктів для української культурології; окресленню основних умов
самовизначення української культури на шляху інтеграції у світовий культурний простір. В статье очерчено основные содержательные границы исследования дилеммы
индивидуализм–коллективизм как основного измерения культурной вариативности. Особое внимание
уделено ключевым понятиям исследования, в частности определению универсальных ценностно–
культурных дефиниций в пределах соизмеримых параметров, которые представлены в
соответствующих научных разработках; определению актуальности исследования данных
конструктов для украинской культурологии; обозначению основных условий самоопределения
украинской культуры на пути интеграции в мировое культурное пространство. This article outlines the main substantive research beyond the dilemma of individualism–collectivism
as an essential dimension of cultural variability. Particular attention is paid to the key concept of the study,
including the definition of universal cultural definitions within spivvymirnyh parameters, determining the
relevance of research data konstuktiv for Ukrainian culture and the formation of the basic conditions for self
Ukrainian culture's integration into the global cultural space.
The author analyzes the scientific literature on the research topic and draws conclusions that scientists have
different definitions universal cultural definitions, most of which are combined to a topic, which was formed as a
result of their understanding within the correlative parameters, the polar clusters (G. Hofstede) binary
oppositions values (K. Klakhon) dichotomies, continuum (A. Zharov), values and cultural dilemmas (F.
Trompernaars, J. Krasnoholova) and others. In most modern developments focuses on the study of the
continuum of individualism–collectivism. The main theoretical and methodological foundations of the study of
individualism – collectivism developed within Western Studies: labor F. Klakhona, F. Strodbeka, D. Matsumoto,
H. Triandis, F. Trompenaarsa, S. Schwarz, G. Hofstede et al. Among the Russian research achievements deserve
special attention A. Zharov, Y. Knyazev, N. and J. Latova, A. Sasa et al. Ukraine has attracted the attention of
labor T. Kamenska, A. Maximova, E. Mouradian, S. Pochebut, I. Meyzhys et al. Studies of individualism–
collectivism will help answer basic questions, without which it is impossible to speak about the search for
adequate solutions to today's challenges socially significant problems facing the Ukrainian culture.